2014
DOI: 10.1016/j.proeng.2014.06.159
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how the Components of a Synthetic Turf System Contribute to Increased Surface Temperature

Abstract: Surface temperatures of synthetic turf have become a factor of growing interest and concern, particularly in warmer regions like Australia. However, it is unclear which components of the synthetic turf system contribute to surface temperature. The aim of this paper was to compare the surface temperature of 34 different synthetic turf products that were exposed to the same environmental conditions to ascertain which components of the synthetic turf system and which environmental factors contributed to increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…37 For example, 59 of the 108 (55%) samples collected at a university football facility tested positive for either MRSA or methicillin-susceptible Staphylococcus aureus . 39 Moreover, the threat of infection extends beyond the locker room, as the physical nature of football provides multiple opportunities for the spread of MRSA from 1 infected/colonized individual to another, to the turf surface, and subsequently, to another player. The abrasive nature of synthetic turf can play a significant role in the onset of MRSA infections, as contact with synthetic turf surfaces can result in turf abrasions 3 that represent a portal of entry for MRSA.…”
mentioning
confidence: 99%
“…37 For example, 59 of the 108 (55%) samples collected at a university football facility tested positive for either MRSA or methicillin-susceptible Staphylococcus aureus . 39 Moreover, the threat of infection extends beyond the locker room, as the physical nature of football provides multiple opportunities for the spread of MRSA from 1 infected/colonized individual to another, to the turf surface, and subsequently, to another player. The abrasive nature of synthetic turf can play a significant role in the onset of MRSA infections, as contact with synthetic turf surfaces can result in turf abrasions 3 that represent a portal of entry for MRSA.…”
mentioning
confidence: 99%
“…38 This reduction of temperature may be caused by the differences in composition and by the chromatic heterogeneity of TPE compared to SBR rubber, 35,36,38 which allows this material a greater heat absorption capacity than TPE. 37 However, the thermal advantages associated with this TPE infill are minimised by a deficient mechanical behaviour, 15 especially in aspects related to traction (lower vertical accelerations and more horizontal acceleration than natural grass). 60 Regarding the interaction effect of weekly use with the installed infill in surface temperature, several researches have shown that greater intensity of field use causes changes in their performance in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…These results also underscore the importance of allowing exemptions from mandated water budgets for ''special landscape areas'' which include recreational turfgrass (sports fields and parks), edibles, and plants irrigated with recycled water. Research indicates that living turfgrass surfaces perform better than synthetic (artificial) surfaces under recreational wear, particularly in hotter climates (Petrass et al, 2014). Artificial surfaces also tend to result in more player injuries (McNitt et al, 2008;Serensits et al, 2011;Williams and Pulley, 2003).…”
Section: Unitsmentioning
confidence: 99%